2017
DOI: 10.18632/oncotarget.15317
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA PTENP1 functions as a ceRNA to modulate PTEN level by decoying miR-106b and miR-93 in gastric cancer

Abstract: Recent studies have shown that competing endogenous RNAs (ceRNAs) play an important role in the regulation of gene expression, and participate in a wide range of biological processes, including carcinogenesis. Long non-coding RNA PTENP1, the pseudogene of PTEN tumor suppressor, has been reported to exert its tumor suppressive function via modulation of PTEN expression in many malignancies. However, whether a PTENP1∼miRNA∼PTEN ceRNA network exists and how it functions in gastric cancer (GC) remains elusive. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 29 publications
2
82
0
Order By: Relevance
“…31 These previous studies indicated the promotive effect of miR-17-5p and the suppressive effect of PTEN on GC, which was in line with our results. 20 Our results indicated a similar mechanism that HOTAIRM1 elevated PTEN expression through binding miR-17-5p. 32 Furthermore, some lncRNAs were supposed to act as competing endogenous RNAs to mediate important genes in human cancer.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…31 These previous studies indicated the promotive effect of miR-17-5p and the suppressive effect of PTEN on GC, which was in line with our results. 20 Our results indicated a similar mechanism that HOTAIRM1 elevated PTEN expression through binding miR-17-5p. 32 Furthermore, some lncRNAs were supposed to act as competing endogenous RNAs to mediate important genes in human cancer.…”
supporting
confidence: 70%
“…17 PTEN loss was associated with the poor response to trastuzumab treatment of GC. 20 Considering the crucial functions of miR-15-7p and PTEN in GC, they were studied in our research to investigate their connections with differentially expressed lncRNA in GC. 19 It was also suggested to be modulated by lncRNA PTENP1 which sponged miR-106b and miR-93 in GC.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the lncRNA-miRNA-mRNA regulatory network is widely recognized; in this network, lncRNA acts as a natural miRNA sponge (ceRNA) to sponge miRNAs, thus decreasing the expression of miRNA targets and affecting posttranscriptional regulation [32]. For example, it is reported that lncRNA PTENP1 functioned as a ceRNA to modulate PTEN levels by decoying miR-106b and miR-93 in gastric cancer [33]. Similarly, Wang et al found that lncRNA TUG1 promotes migration and invasion by acting as a ceRNA of miR-335-5p in osteosarcoma cells [34].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…In gastric cancer, PTENP1 acts as a competing endogenous decoying miR‐106b and miR‐93, resulting in PTEN high expression . In addition, down‐regulation of PTENP1 promotes malignant behaviors in head and neck squamous cell carcinoma …”
Section: Lncrnas In Hallmarks Of Cancermentioning
confidence: 99%
“…57,58 In gastric cancer, PTENP1 acts as a competing endogenous decoying miR-106b and miR-93, resulting in PTEN high expression. 59 In addition, down-regulation of PTENP1 promotes malignant behaviors in head and neck squamous cell carcinoma. 60 The lncRNA HEIH is highly expressed in hepatitis B virus-related hepatocellular carcinoma and plays an important role in G0/G1 arrest.…”
Section: Evading Growth Suppressorsmentioning
confidence: 99%